2016
DOI: 10.3233/bmr-150650
|View full text |Cite
|
Sign up to set email alerts
|

Multi-disciplinary Orthopaedics Rehabilitation Empowerment (MORE) program: A new standard of care for injured workers in Hong Kong

Abstract: The MORE Program which emphasizes early intervention and early MRI screening, is shown to be effective in shortening sick leave and improving RTW outcomes of injured workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…psychoeducation. Other interventions more generally reported the use of psychological and/or behavioural principles (27.5% of studies) (Becker, Angerer, Weber, & Muller, 2020 ; Beemster, van Bennekom, van Velzen, Frings-Dresen, & Reneman, 2020 ; Bergstrom, Bergstrom, Hagberg, Bodin, & Jensen, 2010 ; Bramberg, Bergstrom, Jensen, Hagberg, & Kwak, 2017 ; Brendbekken et al, 2017 ; Brendbekken, Vaktskjold, Harris, & Tangen, 2018 ; Brox et al, 2010 ; Caby et al, 2016 ; Hammond et al, 2017 ; Hampel & Tlach, 2015 ; Hardison & Roll, 2017 ; Hartfiel et al, 2017 ; Hutting et al, 2015 ; Law et al, 2016 ; Lebon, Rongières, Apredoaei, & Delclaux, 2017 ; Lindholdt et al, 2017 ; McCubbin et al, 2014 ; Sandsjo et al, 2010 ; Sullivan & Simon, 2012 ; Sullivan & Adams, 2010 ; Sullivan, Adams, & Ellis, 2012 ; Tan et al, 2016 ; van Vilsteren et al, 2017a ; van Vilsteren et al, 2017b ; Westman et al, 2010 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…psychoeducation. Other interventions more generally reported the use of psychological and/or behavioural principles (27.5% of studies) (Becker, Angerer, Weber, & Muller, 2020 ; Beemster, van Bennekom, van Velzen, Frings-Dresen, & Reneman, 2020 ; Bergstrom, Bergstrom, Hagberg, Bodin, & Jensen, 2010 ; Bramberg, Bergstrom, Jensen, Hagberg, & Kwak, 2017 ; Brendbekken et al, 2017 ; Brendbekken, Vaktskjold, Harris, & Tangen, 2018 ; Brox et al, 2010 ; Caby et al, 2016 ; Hammond et al, 2017 ; Hampel & Tlach, 2015 ; Hardison & Roll, 2017 ; Hartfiel et al, 2017 ; Hutting et al, 2015 ; Law et al, 2016 ; Lebon, Rongières, Apredoaei, & Delclaux, 2017 ; Lindholdt et al, 2017 ; McCubbin et al, 2014 ; Sandsjo et al, 2010 ; Sullivan & Simon, 2012 ; Sullivan & Adams, 2010 ; Sullivan, Adams, & Ellis, 2012 ; Tan et al, 2016 ; van Vilsteren et al, 2017a ; van Vilsteren et al, 2017b ; Westman et al, 2010 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…More frequently, outcomes addressed sickness absence and return-to-work. Examples of measures of sickness absence and return-to-work include self-reported number of workdays lost due to absence (Andersen et al, 2016 ; Beemster et al, 2020 ; Hampel & Tlach, 2015 ; Law et al, 2016 ; Poulain et al, 2010 ; Rasmussen et al, 2016 ; Jensen et al, 2012a ; Gismervik et al, 2020 ; Knapp et al, 2015 ; Soler-Font et al, 2019 ), patient registered data (Bergstrom et al, 2010 ; Bergström et al, 2012 ; Brendbekken et al, 2018 ; Busch et al, 2018 ; Jensen et al, 2012b ; Jorgensen et al, 2011 ; Odeen et al, 2013 ; Ree et al, 2016 ; Reme et al, 2016 ; Stein & Miclescu, 2013 ) or disability payments made (Bergstrom et al, 2010 ; Busch et al, 2011 ; Gross et al, 2017 ; Hara, Bjørngaard, Brage et al, 2018 ; Ibrahim et al, 2019 ; Jensen et al, 2011 ; Marchand et al, 2015 ; Myhre et al, 2014 ). Other outcomes, some of which were also indicators of return-to-work status, broadly measured the ability to participate in and be productive in work, including self-reported work ability ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies addressed service fragmentation between doctors and allied health workers in managing IOD cases in public hospitals in Hong Kong and evaluated their proposed programs, applying the case management approach. 21 , 22 , 23 Nevertheless, their focus was on program evaluation rather than patient epidemiology or risk factor identification. This study draws an overall picture of the characteristics of all‐cause IOD cases and explores risk factors specific to Hong Kong and its unique social, cultural and healthcare environments.…”
Section: Discussionmentioning
confidence: 99%
“…We found that EAGER leads to an increase in a multifaceted approach to chronic LBP. Other studies that have shown that such care plans can lead to an increase in patients returning to work,23 improved range of motion, strength and Visual Analogue Scale scores,37 and reduction of disability 38 39. This markedly contrasts with ESI alone, which has not been found to be effective for long-term relief, to affect surgical rates significantly or to reduce opioid usage among patients with chronic LBP 14.…”
Section: Discussionmentioning
confidence: 99%
“…This comprehensive health management approach includes PT, behavioural therapy and lifestyle modifications. Several studies have shown benefit from such multidisciplinary approaches to chronic LBP compared with routine conservative treatment and analgesics, including better comparative effects on long-term pain and disability 22–25…”
Section: Introductionmentioning
confidence: 99%